Management of Musical Ensemble Learning at JuniorHigh School Hj Isriati Baiturrahman 2 Semarang - Ruswadi, Slamet (2012)
The objective of this research is to describe (1) the design of musical ensemble learning room at Junior High School Hj Isriati Baiturahman 2 Semarang; (2) the material of musical ensemble learning at Junior High School Hj Isriati Baiturahman 2 Semarang; and (3) the musical ensemble learning interaction at Junior High School Hj Isriati Baiturahman 2 Semarang. It is a qualitative research using ethnography design. This study is conducted at Junior High School Hj. Isriati Baiturrahman 2 Semarang. The main subjects of this study are the principal, teacher, and student at Junior High School Hj. Isriati Baiturrahman 2 Semarang. Data collection method uses interview, observation, and documentation. Data analysis is started from (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusion. Data validity test uses credibility, transferability, conformability, and dependability. The result of this study includes (1) the musical ensemble learning room at Junior High School Hj. Isriati Baiturahman 2 Semarang is well-designed. The room is designed based on the student's need in an Air Conditioner room. The room is far from the classroom and the crowd so students are more concentrated to the musical ensemble learning. But the room does not have an LCD that can display songs notation taught by teacher. The arrangement of the musical instrument and music player is made by the arc formation. (2) The musical ensemble learning material of Junior High School Hj. Isriati Baiturahman 2 is well-managed. The material is compiled based on the curriculum. The main materials which must be mastered by student are reading the notation and playing the musical instrument. The materials are from the music books which are arranged by Purwacaraka and Adi MS, continuous practice, and also drill method. (3) Musical ensemble learning at Junior High School Hj. Isriati Baiturahman 2 Semarang is interactive. Teacher and student are together to tune the musical instrument used. Teacher practice directly how to play the music and then followed by student. Each sign given by teacher is always practiced by student, so it gets an integrated musical ensemble. Several techniques used by teacher in the ensemble learning include intensive practice, and also to give the more practice than theory. These techniques makes student to be active, discipline, and also responsible. But not all students are active in the musical ensemble learning.